Structural and functional cardiac changes in endomyocardial fibrosis treated with endomyocardial resection: Disease progression captured by multimodality imaging. Issue 9 (22nd July 2021) - Gibson, Gregory T.; Majure, David T.; Hartman, Alan; Vitkovski, Taisia; Breuer, Frank; Maybaum, Simon; Kuvin, Jeffrey T.; Saba, Shahryar G.
Abstract: Eosinophilic myocarditis, a rare and under‐recognized disease process, occurs due to cytotoxic inflammation of the endomyocardium that over time may lead to a restrictive cardiomyopathy. We report clinical, multimodality imaging, and pathologic findings in a 45‐year‐old woman over a 17‐month period as she progressed from suspected acute eosinophilic myocarditis to phenotypic endomyocardial fibrosis resulting in recurrent ascites. Interval echocardiograms demonstrate definitive pathologic structural changes that reflect the hemodynamic consequences of the underlying cardiomyopathy. Despite a negative myocardial biopsy, characteristic findings on cardiovascular magnetic resonance imaging clarified the diagnosis which led to successful treatment with endomyocardial resection and valve replacements.